1‐Alkyl‐2‐{(O‐Thioalkyl)Phenylazo}Imidazole Complexes of PbII and Their Photochromic Property. Issue 10 (19th June 2013) - Saha Halder, Shefali; Roy, Suman; Kumar Mondal, Tapan; Saha, Rajat; Sinha, Chittaranjan
Abstract PbII complexes of 1‐alkyl‐2‐{(o‐thioalkyl)phenylazo}imidazole (SRaaiNR'), [Pb(SRaaiNR')2X2] were characterized by spectroscopic studies. The single‐crystal X‐ray structure of [Pb(SEtaaiNEt)2Cl2] (SEtaaiNEt = 1‐ethyl‐2‐{(o‐thioalkyl)phenylazo}imidazole) proved imidazolyl‐N and –SEt coordination forming unusual puckered eight member chelate rings. UV light irradiation of the complexes in DMF solution shows E‐to‐Z (E and Z refer to trans and cis‐configuration about –N=N–, respectively) photoisomerization of the coordinated azoimidazole. The rate of isomerization follows the sequence: [Pb(SRaaiNR')2Cl2] < [Pb(SRaaiNR')2Br2] < [Pb(SRaaiNR')2I2]. Quantum yields (φE→Z) and the activation energy (Ea) of the isomerization of the complexes are lower than observed for the free ligand. This can be explained by considering the molecular assembly and the thus observed increase in mass and rotor volume of the complexes. DFT and TDDFT calculations of optimized geometry could explained the spectral properties and photochromic activity.